Greater γ-tocopherol status during acute smoking abstinence with nicotine replacement therapy improved vascular endothelial function by decreasing 8-iso-15(S)-prostaglandin F2α. (April 2015) - Mah, Eunice; Pei, Ruisong; Guo, Yi; Masterjohn, Christopher; Ballard, Kevin D; Taylor, Beth A; Taylor, Alan W; Traber, Maret G; Volek, Jeff S; Bruno, Richard S
Nicotine replacement therapy (NRT) improves the long-term success rate of smoking cessation, but induces oxidative stress and inflammatory responses that may delay the restoration of vascular endothelial function (VEF). No studies have examined co-therapy of NRT-assisted smoking abstinence with γ-tocopherol (γ-T), a vitamin E form with antioxidant and anti-inflammatory activities, on improvements in VEF. In a randomized, double-blind, placebo-controlled study, healthy smokers (25 ± 1 y old; mean ± SEM) received NRT and abstained from smoking for 24 h with placebo ( n = 12) or oral administration of γ-T-rich mixture of tocopherols (γ-TmT; n = 11) that provided 500 mg γ-T. Brachial artery flow-mediated dilation (FMD), and biomarkers of nitric oxide metabolism, antioxidant status, inflammation, and lipid peroxidation [8-iso-prostaglandin F2α stereoisomers (8-iso-15(R)-PGF2α and 8-iso-15(S)-PGF2α )] were measured prior to and after 24 h of smoking abstinence. Smoking abstinence with NRT regardless of γ-TmT similarly decreased urinary naphthol ( P < 0.05) without affecting plasma cotinine. γ-TmT increased plasma γ-T by 4-times and the urinary metabolite of γ-T, γ-carboxyethyl-chromanol, by three times. Smoking abstinence with γ-TmT, but not smoking abstinence alone, increased FMD without affecting plasma nitrate/nitrite or the ratio of asymmetric dimethylarginine/arginine. Urinary 8-iso-15(S)-PGF2α decreased only in those receiving γ-TmT and was inversely correlated to FMD ( R = −0.43, P < 0.05). Circulating markers of inflammation were unaffected by smoking abstinence or γ-TmT. Short-term NRT-assisted smoking abstinence with γ-TmT, but not NRT-assisted smoking abstinence alone, improved VEF by decreasing 8-iso-15(S)-PGF2α, a vasoconstrictor that was otherwise unaffected by NRT-assisted smoking abstinence.